Foreign Direct Investment and Economic Development: Comparative Analysis in Southeast Asia - Afifah Salim; Jumrahana; Iqra Aiman (Mustard Journal De Ecobusin, 2025)
This study examines the role of Foreign Direct Investment (FDI) in shaping economic development across selected Southeast Asian countries. Using a comparative analysis, it highlights the uneven impact of FDI inflows by analyzing variations in volume, sectoral distribution, and institutional quality. Data from Singapore, Vietnam, Indonesia, the Philippines, and Cambodia reveal that while FDI contributes significantly to growth, its benefits are not uniform across the region. Singapore has leveraged its institutional strength and advanced services sector to attract high-value investment, whereas Vietnam has successfully used FDI to accelerate manufacturing-led industrialization. By contrast, Indonesia and the Philippines struggle to convert large inflows into proportional developmental outcomes due to regulatory inefficiencies, while Cambodia remains highly dependent on resource-based FDI, exposing it to sustainability risks. The findings underscore that the developmental impact of FDI depends less on the quantity of inflows than on sectoral orientation, absorptive capacity, and governance effectiveness. Theoretically, the study challenges the linear assumption that FDI automatically drives growth, while practically, it suggests that Southeast Asian countries need to strengthen human capital, institutional frameworks, and regional cooperation to maximize developmental returns.